’n Prakties-teologiese ondersoek na die uitwerking van afwesige vaders: ’n verkennende kwalitatiewe ondersoek in die Promosa-gemeenskap - Freeks, F. E. (Koers, 2009)
A practical theological investigation into the effect of absent fathers: an exploratory qualitative investigation in the Promosa community In this article it is shown that empirical research can be used to confirm important findings in literature studies about the understanding of absent fathers and the devastating conse-quences such as social problems, socio-economic problems and psychological problems. A literature study was done on the role of the father and all the relevant aspects are viewed in a broader context. The results obtained through a qualitative investigation of eight women from Promosa (Potchefstroom) as a focus group confirmed the trends found in the preliminary literary research. The outcomes may have important implica-tions in the field of practical theology and pastoral guidance for absent fathers, the women involved with those fathers and fatherless children. Some guidelines are proposed towards an effort to help fathers to become more involved.